Avaliação de ações educacionais de educação especial em um município paulista de pequeno porte - Vertuan, Greice de Souza (2021)
In the 21st century, in the Brazilian scenario, the National Education Plan (2014-2024) proposes, among other goals, goals for the educational attendance of the Special Education Target Audience (SETA), without, however, an evaluation instrument is available to analyze the specific situation of this public. In this context, the objective of this research was to evaluate aspects of the special education policy indicated by Goal 4 of the NEP (2014/2024), with the general objective of evaluating Special Education practices in regular schools in a small municipality in the state of São Paulo , from the perspective of SETA students, family members of SETA students, teachers of the common room and the Multifunctional Resource Room (MRR), support team, multidisciplinary team and managers, from their responses to an applied questionnaire used as an instrument evaluation. The questionnaire was analyzed from a qualitative and quantitative perspective in order to study and understand the effectiveness of educational inclusion actions, constituting this as an exploratory-descriptive, case study type. For this study, 4 axes of analysis were chosen: training, planning, pedagogical actions and evaluation; that emerged from the previous reading of the questionnaires, which allowed the understanding of the situation of Special Education in the municipality in question. Based on the analysis axes, it was possible to discuss 10 of the 19 strategies proposed by the PNE in Goal 4, however, the questionnaire would allow the analysis of 16 strategies. The instrument can be considered efficient for the assessment of Special Education in a municipality, however, its application had some limitations. In this analysis, it was still possible to verify the instrument's limitation in collecting data with more quantitative than qualitative aspects, in addition to the extension of some questionnaires, which made its application difficult. The use of questionnaires has shown the need to listen to the various actors in order to better understand the quality of education offered to SETA, the relevance of this instrument as an evaluation of education and support for the elaboration of public education policies, as well as the possibility of improvement for data collection. The need to evaluate the education offered to the SETA student is highlighted, since he has had access to regular schools, but his learning, when we think about the quality of teaching, and the universalization of services, as recommended by Goal 4, are still unsatisfactory.